2022
DOI: 10.21203/rs.3.rs-2315989/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Impacts of the COVID-19 Pandemic on Subway Ridership and on the Interactions with other Transportation Modes

Abstract: The COVID-19 pandemic has led governments to implement restrictive policies which have caused unprecedented effects on transportation systems. This paper assesses which measures had more impacts on subway daily ridership in Montreal (Quebec, Canada) and on the interactions between modes using time series approaches. Change point detection methods, based on regression structure and Bayesian posterior probabilities, are first applied to automatic fare collection (AFC) data available from January 2019 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Among all the subjects that have been raised in relation to COVID-19, resilience is widely studied. Deschaintres et al (2022) studied daily time series of PT demand and identified breakpoints, corresponding to the implementation of health policies. At a more disaggregated level, they compared different periods of the day and types of days.…”
mentioning
confidence: 99%
“…Among all the subjects that have been raised in relation to COVID-19, resilience is widely studied. Deschaintres et al (2022) studied daily time series of PT demand and identified breakpoints, corresponding to the implementation of health policies. At a more disaggregated level, they compared different periods of the day and types of days.…”
mentioning
confidence: 99%